Al-Maharat al-Asasiyah al-Azamah li Ta’lim al-Lughah al-Arabiyah fi al-marhalah al-Ibtidaiyah/Basic Skills And Strategies Needed For Teaching Arabic Language at Primary School Level - Ahmad Garba (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
This paper aims to highlight the importance of the basic teaching skills in teaching Arabic language to teachers in primary schools and it impact on improving teachers' performance in discharging their duties in the teaching profession and raising the level of their competence and abilities in building learners' personalities. The researcher used a descriptive method to carry out this study, as well as observation tool as the instrument for the study. The research concluded that these basic skills are effectively good in teaching and learning Arabic language, especially in primary schools level, The teaching process does not dispense with the necessary basic skills, which are the basis on which teachers build their activities in the classroom to send information and ideas to the minds of learners, and these skills are not effective only inside the classroom, but even outside it. The primary objective behind choosing this topic is to outline the role and impact of the basic teaching skills to the student-teachers and also the practicing teachers, especially those engage in teaching Arabic language in basic school level, These basic skills include: the skill of set induction, skill of classroom management, skill of asking questions, skill of reinforcement, skill of using chalkboard, and the skill of using various teaching method.المستخلص: تهدف هذه الورقة إلى تسليط الضوء عن أهمية المهارات التدريس الأساسية لدى معلمي اللغة العربية في المدارس الإبتدائية ومدى تأثيرها في تحسين أداء المعلمين في إنجاز واجباتهم في مهنة التعليم ورفع مستوى كفاءتهم وقدراتهم في بناء شخصيات المتعلمين، استخدم الباحث المنهج الوصفي لإجراء هذا البحث كما استخدم الأداة الملاحظة لحصول على المعلومات الملائمة، وكما استنتجت هذه الدراسة الى إبراز فاعلية هذه المهارات الأساسية في عملية التعليمية وخاصة في المرحلة الابتدائية. ولا تستغني عملية التدريس عن المهارات الأساسية الازمة، وهي الأساس التي يبني عليها المدرسين عملياتهم داخل الفصل لإرسال المعلومات والأفكار إلى أذهان المتعلمين، وهذه المهارات لم تقف داخل الغرفة الصف فحسب،بل حتى خارجها، وهذه هي الباعثة التي من أجلها أراد الباحث اختيار هذا الموضوع ليبحث عن تلك المهارات الآزمة، ومن هذه المهارات الأساسية: مهارة التهيئة للدرس، ومهارة إدارة الفصل، ومهارة طرح الأسئلة ومهارة التعزيز ومهارة استخدام السبورة ومهارة استخدام الطرق التدريس المتنوعة، وتحتوي هذه الورقة الي مقدمة ومنهجية البحث ومفهوم التدريس وأهمية المهارات التدريس ثم البيان حول بعض المهارات التدريس الأساسية في عملية التدريس ثم نتائج البحث والمقترحات والخاتمة والمراجع.